2015
DOI: 10.1007/s00595-015-1280-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided ilioinguinal/iliohypogastric block did not reduce emergence delirium after ambulatory pediatric inguinal hernia repair: a prospective randomized double-blind study

Abstract: UMIN000008586.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 26 publications
1
26
0
1
Order By: Relevance
“…Now, peripheral nerve blocks are being used more widely as post-operative analgesic modalities in children 12 and they can be safely placed under general anaesthesia. 14 In this study, we were able to maintain similar, end-tidal concentrations of sevoflurane during surgery, without a significant fluctuation of blood pressure, in both the remifentanil and block groups. In contrast, pre-incisional ultrasound-guided ilioinguinal/iliohypogastric nerve blocks did not reduce EA after ambulatory paediatric hernia repair, although nerve block decreased the amount of intraoperative sevoflurane needed.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Now, peripheral nerve blocks are being used more widely as post-operative analgesic modalities in children 12 and they can be safely placed under general anaesthesia. 14 In this study, we were able to maintain similar, end-tidal concentrations of sevoflurane during surgery, without a significant fluctuation of blood pressure, in both the remifentanil and block groups. In contrast, pre-incisional ultrasound-guided ilioinguinal/iliohypogastric nerve blocks did not reduce EA after ambulatory paediatric hernia repair, although nerve block decreased the amount of intraoperative sevoflurane needed.…”
Section: Discussionmentioning
confidence: 59%
“…In contrast, pre-incisional ultrasound-guided ilioinguinal/iliohypogastric nerve blocks did not reduce EA after ambulatory paediatric hernia repair, although nerve block decreased the amount of intraoperative sevoflurane needed. 14 In this study, we were able to maintain similar, end-tidal concentrations of sevoflurane during surgery, without a significant fluctuation of blood pressure, in both the remifentanil and block groups. A pre-incisional blockade of the major scalp nerves and/or infiltration of anaesthesia around the nevi can block nociceptive pain arising from the wound completely for a few hours.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Three studies assessed the use of ilioinguinal/iliohypogastric nerve blocks in children undergoing inguinal surgeries. 45 , 55 , 64 One study reported postoperative pain (CHIPPS) in the post-anesthesia care unit (PACU) was significantly higher in the local anesthetic group compared with the ilioinguinal/iliohypogastric nerve block group. Another study compared intraoperative ultrasound-guided ilioinguinal/iliohypogastric nerve blocks with those who did not receive a block on postoperative analgesic outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…A prospective randomized, double-blind study of children (1-6 yr) showed that ilioinguinal/ iliohypogastric blocks did not decrease ED after a sevoflurane anaesthetic, despite equal pain relief between those with and without blocks. 72…”
Section: Regional Anaesthesiamentioning
confidence: 99%